Students’ Perceptions Toward The Methods of English Language Teaching For The Fourth Semester Students Of Management Department At UKI Toraja - Shilfani Shilfani; Meikhel Yoes Ruruk Gotti (LPPM UKI Toraja, 2021)
The objectives of this research are (1) to find out the methods are used by the lecturer in English Language Teaching for the fourth semester students of Management department at UKI Toraja, (2) to find out the students’ perceptions toward the method in English Language Teaching for the fourth semester students of Management department at UKI Toraja. The informants of this study were the fourth semester students of Management Department who had programmed English courses. The writer used snowball sampling to collecting data. There are 16 students as research informants. The writer collected the data by conducting semi-structural interviews. After transcribe the interview result, the writer apply qualitative method by Miles and Huberman technique in order to analyze the data. The data was collected from the fourth semester students of Management Department at UKI Toraja still active in that university. There were 16 students who have been interviewed and they have programmed English courses. The interview was held in Tana Toraja, on Wednesday 15th July 2020 untill on Tuesday 21st July 2020. The resut of this research are the methods used by lecturer in English Language Teaching in the fourth semester students of Management Department at UKI Toraja are reading methods and the silent way while the student’s perceptions toward the method used by lecturer in English Language Teaching in the fourth semester students of Manegement Department at UKI Toraja is Negative perception the methods are less effective in English Language Teaching, students felt bored, students felt scared and nervous in English Language Teaching and sometimes do not understand the material taught by the Lecturer. Based on the results above, the writer concludes that there are two methods are used by English lecturer in English Language Teaching and there are some perception (Negative Perception) from the students as mention above.